2020
DOI: 10.1186/s12284-020-0367-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ineffective Haplotypes at the Rice Blast Resistance (R) Gene Loci in Chinese Elite Hybrid Rice Varieties Revealed by Sequence-Based Molecular Diagnosis

Abstract: Multiple haplotypes at the same rice blast R-gene locus share extremely high sequence similarity, which makes the gene diagnostic method using molecular markers less effective in differentiation from one another. The composition and distribution pattern of deployed R genes/haplotypes in elite rice varieties has not been extensively analyzed. In this study, we employed PCR amplification and sequencing approach for the diagnosis of R-gene haplotypes in 54 Chinese elite rice varieties. A varied number of function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The gradual replacement of Wx a and Wx lv by Wx b in the female parents might be the main reason for the quality improvement of hybrid rice. In recent years, blast resistance and superior grain quality have become two of the most important goals in rice breeding in China, as the former is essential for varietal releasing in the certificating system and the latter has higher market price (Senapati et al., 2011; Xiao et al., 2020). R608, Huahui 4, R1141, 93–11 and Huazhan, as parental lines used in our breeding programme, are five elite restorer lines for hybrid rice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gradual replacement of Wx a and Wx lv by Wx b in the female parents might be the main reason for the quality improvement of hybrid rice. In recent years, blast resistance and superior grain quality have become two of the most important goals in rice breeding in China, as the former is essential for varietal releasing in the certificating system and the latter has higher market price (Senapati et al., 2011; Xiao et al., 2020). R608, Huahui 4, R1141, 93–11 and Huazhan, as parental lines used in our breeding programme, are five elite restorer lines for hybrid rice.…”
Section: Discussionmentioning
confidence: 99%
“…From 2008 to 2021, a total of 153 hybrid varieties derived from Huazhan have been released in China (http://www.ricedata.cn/variety/). These two restorer lines were previously reported to contain multiple R genes and confer resistance to many Magnaporthe oryzae strains (Lei et al., 2013; Ma et al., 2014; Tian et al., 2016; Wu et al., 2017; Xiao et al., 2020; Yang et al., 2009). However, we found both of them showed moderately to highly susceptible reactions in some blast hotspots of Hunan province, China, in recent years, whereas Gumei 4, the donor of Pigm , displayed stable resistance to rice blast (Y.…”
Section: Discussionmentioning
confidence: 99%
“…S1). The 12 novel AVR-Pib haplotypes (H01-H12) were identi ed compared to previous published alleles [3,27]. Alignment of DNA sequence assemblies of the AVR-Pib gene from 90 isolates revealed 18 mutation sites, including six mutant sites in the CDS region which weren't in the signal-peptide region (Table 2; Additional le 5 and 6: Fig.…”
Section: Virulence Function Of Avr-pib Variations Against the Pib Genementioning
confidence: 99%
“…Those results showed that the Pib gene exhibits different resistance to Chinese rice blast from different rice-growing regions. There were 42 out of 54 varieties containing Pib in Chinese elite hybrid rice varieties, two haplotypes of Pib were identi ed, and 9 different haplotypes of AVR-Pib were found among 27 M. oryzae [27]. The reactions of differential isolates on 54 rice varieties between the frequency of AVR-Pib haplotypes in the differential isolates showed a good correlation [27].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation